The feasibility of low-concentration contrast and low tube voltage in computed tomography perfusion imaging: an animal study. Issue 1 (10th January 2018) - Pan, Yuning; Song, Aiqin; Bu, Shizhong; Chen, Zhaoqian; Huang, Qiuli; Li, Aijing
Abstract : Aim: To investigate the feasibility of low-concentration contrast (270 mg/ml) together with low tube voltage (80 kV) and adaptive iterative dose reduction (AIDR)-3D reconstruction in liver computed tomography (CT) perfusion imaging. Method: A total of 15 healthy New Zealand rabbits received two CT scans each. The first scan (control) was acquired at 100 kV and 100 mA with iopromide (370 mg/ml), while the second scan (experimental) was acquired at 80 kV and 100 mA with iodixanol (270 mg/ml) 24 h after the first scan. The obtained images were reconstructed with filtered back projection (FBP) and AIDR-3D in the control and experimental groups respectively. The perfusion parameters (hepatic artery perfusion [HAP], portal vein perfusion [PVP], hepatic perfusion index [HPI], and total liver perfusion [TLP]) and image quality (image quality score, average CT value of abdomen aorta, signal-to-noise ratio [SNR], contrast-to-noise ratio [CNR], and figure of merit [FOM]) were compared using a paired t -test or Mann–Whitney U test between the two groups, when appropriate. The effective radiation dose and iodine intake were also recorded and compared. Results: With the exception of the FOM criteria, the image quality and perfusion parameters were not significantly different between the two groups. The effective radiation dose and iodine intake were 38.79% and 27.03% lower respectively, in the experimental group. Conclusion: Low-concentration contrast (iodixanol, 270 mg/ml) together with low tube voltage (80 kV) and AIDR-3D reconstruction help to reduce radiation dose and iodine intake without compromising perfusion parameters and image quality in liver CT perfusion imaging.